Предмет: Алгебра,
автор: наташа16
решите уравнение
(х+1)^2=16
(x-1)^2=0
(x-5)^2=1
(2x-1)^2=4
(3x+6)^2=100
(3-2x)^2=25
Ответы
Автор ответа:
0
(х+1)^2=16 х + 1 = +-4 х₁ = 4 -1 = 3 х₂ = -4 - 1 = -5
(x-1)^2=0 х - 1 =0 х = 1
(x-5)^2=1 х -5 = +-1 х ₁= 1+5 = 6 х₂ = -1 + 5 = 4
(2x-1)^2=4 2х - 1 = +-2 2х₁ = 2+1 = 3 х₁ = 3/2
2х₂ = -2 + 1 = -1 х₂ = -1/2
(3x+6)^2=100 3х + 6 = +-10 3х₁ = 10 - 6 = 4 х₁ = 4/3
3х₂ = -10-6 = -16 х₂ = -16/3
(3-2x)^2=25 3 - 2х = +-5 2х₁ = 3 - 5 = -2 х₁ = -2/2 = -1
2х₂ = 3 + 5 = 8 х₂ = 8/2 = 4
(x-1)^2=0 х - 1 =0 х = 1
(x-5)^2=1 х -5 = +-1 х ₁= 1+5 = 6 х₂ = -1 + 5 = 4
(2x-1)^2=4 2х - 1 = +-2 2х₁ = 2+1 = 3 х₁ = 3/2
2х₂ = -2 + 1 = -1 х₂ = -1/2
(3x+6)^2=100 3х + 6 = +-10 3х₁ = 10 - 6 = 4 х₁ = 4/3
3х₂ = -10-6 = -16 х₂ = -16/3
(3-2x)^2=25 3 - 2х = +-5 2х₁ = 3 - 5 = -2 х₁ = -2/2 = -1
2х₂ = 3 + 5 = 8 х₂ = 8/2 = 4
Автор ответа:
0
спасибо:)))
Похожие вопросы
Предмет: Информатика,
автор: nagliy257
Предмет: Физика,
автор: kvinikadzebarbara
Предмет: Информатика,
автор: Аноним
Предмет: Алгебра,
автор: makcsokolovskiy
Предмет: Математика,
автор: sabino4kaserikova